On finite-dimensional Banach spaces in which suns are connected - Alimov, Alexey Rostislavovich (Eurasian Mathematical Journal, 2015)
The present paper extends and refines some results on the connectedness of suns in finite-dimensional normed linear spaces. In particular, a sun in a finite-dimensional (BM )-space is shown to be monotone path-connected and having a continuous multiplicative (additive) \(ε\)-selection from the operator of nearly best approximation for any \(ε > 0\). New properties of (BM )-space are put forward.